Soil Bacterial Communities in a Tobacco Field Plantation and Under Different N Fertilizations in Central Yunnan, China - Zhang, Xiaohua; Mu, Yifan; Li, Meiting; Yang, Xin; Zhang, Donghui; Wang, Keqin; Song, Yali (Agronomy (Basel), 2025)
Soil microbial communities contribute to the growth, health, and productivity of crops during agricultural production, and yet it is not clear how different fertilization practices affect the diversity, composition, and co-occurrence network of soil bacterial communities at different stages of growing tobacco. Here, we report the characteristics of changes in soil bacterial communities at different tobacco growth stages and fallow periods after fertilizer application by selecting long-term continuous crop tobacco fields with different fertilizers (control (CK), a cattle manure organic fertilizer (OM), a cattle manure organic fertilizer and chemical fertilizer mix (MNPK), a chemical fertilizer (NPK), and crushed straw (ST)) at the time of tobacco planting, combined with high-throughput sequencing technology and molecular ecological network methods. The results showed that soil bacterial diversity did not respond significantly to fertilizer application during the growing period of roasted tobacco, which only increased bacterial diversity in the fallow period. The key taxa of the co-occurrence network were lost during the peak and maturity periods of tobacco cultivation and were gradually recovered after fallowing. The choice of straw, chemical fertilizer, and cow manure organic fertilizer mixed with chemical fertilizer when planting tobacco can better feed the growth of roasted tobacco, and the choice of an organic matter fertilizer (straw and cow manure) as the base fertilizer can accelerate the repair of the bacterial co-occurrence network after the soil has been fallowed and improve the subhealth of the planted tobacco soil.